Atypical manifestations of chikungunya infection - Rajapakse, S.; Rodrigo, C.; Rajapakse, A. (My University, 2009)
Chikungunya fever is a viral infection transmitted to humans by the bite of infected mosquitoes. Typical chikungunya virus (CHIKV) infection results in an acute febrile illness characterized by severe joint pain and rash. Although chikungunya is generally not considered life threatening, atypical clinical manifestations resulting in significant morbidity have been documented, especially during epidemics. This review describes atypical manifestations following CHIKV infection reported in the literature, categorized as neurological, cardiovascular, skin, ocular, renal and other manifestations. The importance of vertical transmission from an infected mother resulting in neonatal infection is also highlighted. CHIKV infection can result in severe illness needing intensive care, with significant mortality. While there are many deaths reported which are directly attributable to CHIKV infection, background mortality is also increased during epidemics. In this context, considering CHIKV infection a benign and non fatal illness has to be revisited.